Do Stressed Women have Abnormal Glucose Level? - Amirul Adli M.; Gaushinee V.; Abdullah M. S.; Rafaee R.; Syahirah M T.; Amirah M.; Chut Kartika B.; Lily Alma Nadirah A. J.; Sabariah A. H. (International Journal of Public Health Science (IJPHS), 2017)
Stress is a physical, mental and emotional response to a challenging event and is a normal part of everyone's life.  It has been linked to suppression of the immune system and could increase the risk of getting ill or alter the course of existing illness.  Studies show that stress is associated with increased HBA1c, especially in females.  Therefore the purpose of this study was to determine the prevalence of stress with abnormal glucose value among the women community.  A cross-sectional study was conducted among 168 residents of Mukim Sg. Pelek, Sepang, Selangor.  Participants were selected through a simple random sampling and were asked to answer questionnaires provided.  The Depression, Stress and Anxiety (DASS-21) scale was used to determine the prevalence of stress and random blood sugar (RBS) for measurement of the glucose level.  Data was analyzed using Statistical Package Social Sciences (SPSS) version 20 and Chi-square analyses for determining the association between variables.  The study found that 58.3% of the stressed women in the community have abnormal blood glucose level, which indicated that the risk of getting diabetes is slightly high.  This finding has important implication for designing strategic plans for intervention program on awareness towards coping with stress positively.